2011
DOI: 10.5935/1678-9741.20110023
|View full text |Cite
|
Sign up to set email alerts
|

Embolia pulmonar quase fatal, um modelo experimental

Abstract: Embolia pulmonar quase fatal, um modelo experimental: variáveis hemodinâmicas, gasométricas e capnográficasNear-fatal pulmonary embolism in an experimental model: hemodynamic, gasometric and capnographic variables Abstract Introduction: Experimental studies on pulmonary embolism (PE) are usually performed under mechanical ventilation. Most patients with suspicion of PE enter the Emergency Services in spontaneous breathing and environmental air. Thus, under these conditions, measurements of hemodynamic, gasomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…A number of experimental model studies have demonstrated that PaCO 2 does not vary in near-fatal PE. [ 29 ] In the present study, PetCO 2 had a high negative predictive value in excluding PE. [ 30 ] In the diagnosis of high-risk PE, a decrease in PetCO 2 was suggested to be an earlier detection of intraoperative pulmonary emboli.…”
Section: Discussionsupporting
confidence: 51%
“…A number of experimental model studies have demonstrated that PaCO 2 does not vary in near-fatal PE. [ 29 ] In the present study, PetCO 2 had a high negative predictive value in excluding PE. [ 30 ] In the diagnosis of high-risk PE, a decrease in PetCO 2 was suggested to be an earlier detection of intraoperative pulmonary emboli.…”
Section: Discussionsupporting
confidence: 51%
“…It has the same shape of the other gas elimination curves, with the advantage of being obtained with a gas which is normally produced in the body and eliminated by the lungs. 11 , 12 The main variables analyzed were end-tidal concentration of carbon dioxide (ETCO 2 ), Slope of phase 2 (Slp2), and Slope of phase 3 (Slp3) of capnogram. Slp2 represents the rapid increase in CO 2 coming from short paths to alveoli; it comes immediately after the elimination of the air from the dead space.…”
Section: Introductionmentioning
confidence: 99%
“…There are overall very few in vivo models of acute PE and, to our knowledge, none that fulfills all of the criteria above. 14 22 …”
mentioning
confidence: 99%